Helping students overcome depression and anxiety : a practical guide - Merrell, Kenneth W. (Guilford practical intervention in the schools series., 2008)
Presents guidelines for school counselors, psychologists, and others to follow in the intervention and prevention of depression, anxiety, and internalizing problems experienced by students in kindergarten through twelfth grade; and features twenty-six reproducible worksheets.